Effects of hijab as Islamic religious symbol on muslim consumer attitudes towards advertisements - Taheri, Abbas Naseri (2013)
Cues and symbols are effective instruments to remind the consumers of their cultural values’ affiliations. Utilizing these symbols in advertisement might unconsciously enhance information processing and consequently generate a favorable feeling. Hijab as a significant religious cue for Muslims might peripherally influence advertisement evaluative efficacy among Muslim consumers. Utilizing Elaboration Likelihood Model (ELM), this research examined peripheral effect of religious symbol of hijab among Malaysian Muslims. A total of 120 UPM undergraduate students participated in four groups of experiments. They were randomly assigned to the four experimental groups. Participants in each group were exposed to four different TV commercial products portraying spokesperson with or without religious symbol of hijab. The results revealed that advertisements with religious symbol of hijab elicit positive attitude towards advertisement, attitude towards brand and purchase intention than advertisements without religious symbol of hijab. The main effect of religious symbol of hijab among different types of products is not contingent upon the type of product. This study also indicates that religiosity of the respondent has a significant moderating effect on the evaluation of an advertisement that portrays a spokesperson with hijab. That is, degree of religiosity is positively correlated with respondents’ attitude towards advertisement, attitude towards brand, and purchase intention. Furthermore, the influence of hijab as a peripheral cue on Muslims’ perceptions of advertisement even among highly involved respondents shows the significant role of this Islamic cue despite the thoughtful effort dedicated to advertisement messages. These findings challenge the mainstream of the ELM theory which posits that a favorable peripheral cue would not significantly influence the advertisement evaluation among highly involved subjects.